2010
DOI: 10.1002/anie.200906407
|View full text |Cite
|
Sign up to set email alerts
|

Metal Triflimidates: Better than Metal Triflates as Catalysts in Organic Synthesis—The Effect of a Highly Delocalized Counteranion

Abstract: The continuously increasing need for novel and selective methods in organic synthesis to aid drug discovery and to address environmental concerns is a constant source of stimulation to develop novel and more efficient reaction systems. This has often resulted in a focus on transition metals, ligands, and additives, with much less attention paid to the counterion(s) of the metal cation. Recently, metal salts with one or more triflimidate counterion(s) have appeared as a unique class of catalysts that display ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
160
1
17

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 283 publications
(313 reference statements)
4
160
1
17
Order By: Relevance
“…[6] On the other hand, the molecular species HSbF 6 has neverbeen observed. [7] Our research group is interested in the use of Lewis superacids [8] in molecular catalysis, notably N-heterocyclic carbene gallium complexes of type [(NHC)GaX 2 ][SbF 6 ]( X=Cl, Br,I ). [9,10] These compounds are typicallyp repared by mixing (NHC)GaX 3 and AgSbF 6 in 1,2-dichloroethane at room temperature.…”
mentioning
confidence: 99%
“…[6] On the other hand, the molecular species HSbF 6 has neverbeen observed. [7] Our research group is interested in the use of Lewis superacids [8] in molecular catalysis, notably N-heterocyclic carbene gallium complexes of type [(NHC)GaX 2 ][SbF 6 ]( X=Cl, Br,I ). [9,10] These compounds are typicallyp repared by mixing (NHC)GaX 3 and AgSbF 6 in 1,2-dichloroethane at room temperature.…”
mentioning
confidence: 99%
“…We found that LiNTf2 slowed down the reaction in the beginning but could maintain its reactivity effect with time, probably due to the stabilizing effect of NTf2 -. 58,69 NaBARF enhanced the rate of the reaction significantly but only in the beginning. We attributed the time leveling effect of NaBARF to catalyst deactivation under the reaction conditions.…”
Section: Selection Of Reaction Promotersmentioning
confidence: 93%
“…Our work is significant because this tandem chemistry is Recently, cationic metal salts containing triflimidate (NTf2 -) have appeared as a unique class of catalysts that display outstanding -and -Lewis acid character. 58 Consequently, these metal triflimidates often outperform their triflate analogues in catalysis. 58 In 2010, Dalla and Dunach published a review article in Angew.…”
Section: Summary and Future Directionmentioning
confidence: 99%
See 2 more Smart Citations